Satisfaction, Purchasing Behavior, and Customer Loyalty of Butik Emas Logam Mulia - Reza, Fakhri; Sumarwan, Ujang; Hartoyo, Hartoyo (Journal of Consumer Sciences, 2019)
This research study aims to highlights the factors of customer loyalty based on satisfaction, consumer buying behavior at Butik Emas Logam Mulia (BELM) Pulogadung. Using the SERVQUAL services model to analyze quality of services by descriptive statistics method. This study was conducted using 200 respondents selected by purposive. Tangible, empathy, responsiveness, reliability, and assurance (Service Quality Dimensions) were the variables considered for this study. The research found that reliability and responsiveness (not empathy, tangibility, and assurance) impact consumer satisfaction which increases the frequency of purchasing. It explains, a negative relationship between satisfaction and loyalty intensions. Furthermore, both loyalty and satisfaction effects weaken with increased prior consumption experiences, related on organizational issues. Thus, when the customers invest in satisfaction, managers should consider their individual marginal impacts on loyalty and distinguish between consumers with reference to their prior consumption experiences. The managerial implication in marketing strategies to increase customer loyalty, consumer satisfaction is directly related to provide fast, precise, and friendly services in accordance with established service standards. Moreover, the research study concludes that image of a service provider, loyalty of consumers, consumer expectations, perceived value, perceived quality and the way complains are handled are very important factors that determine consumer loyalty levels.